2009
DOI: 10.1017/s0025315409000757
|View full text |Cite
|
Sign up to set email alerts
|

Predation: a regulating force of intertidal assemblages on the central Portuguese coast?

Abstract: Predation has long been recognized as an important biological force driving community patterns in intertidal rocky shores throughout the world. Little is known, however, about the role of predation by mobile marine predators in shaping intertidal prey populations in Portuguese rocky shores. The abundance and population structure of crabs were assessed during nocturnal low-tides on two rocky shores to characterize potential predator species. To assess the effect of predation on intertidal species including limp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Therefore, natural mortality appears to play a minor role in determining the observed fluctuations in limpet abundance and size. This observation is in line with other studies that did not detect a strong influence of natural predation on limpet population sizes, as observed for instance for P. depressa along the coast of Portugal (Brazão et al, 2009;Silva et al, 2004). Further studies specifically designed to assess the intensity of natural predation in the study area would be useful to confirm this hypothesis.…”
Section: The Role Of Natural Predatorssupporting
confidence: 91%
“…Therefore, natural mortality appears to play a minor role in determining the observed fluctuations in limpet abundance and size. This observation is in line with other studies that did not detect a strong influence of natural predation on limpet population sizes, as observed for instance for P. depressa along the coast of Portugal (Brazão et al, 2009;Silva et al, 2004). Further studies specifically designed to assess the intensity of natural predation in the study area would be useful to confirm this hypothesis.…”
Section: The Role Of Natural Predatorssupporting
confidence: 91%
“…Indeed, using predatorexclusion experiments, Silva et al (2008) observed a significant reduction of limpet densities when crabs predation was occurring. Conversely, Brazão et al (2009) failed to detect a significant effect from E.…”
Section: Predatory Behavior Of the Crab Eriphia Verrucosamentioning
confidence: 80%
“…According to the food habits of this intertidal predator (Rossi and Parisi 1973;Brazão et al 2009;Silva et al 2010), six prey species were chosen as potential food items. The oyster Magallana angulata (Lamarck, 1819), the mussel Mytilus galloprovincialis Lamarck, 1819 and the limpet Patella depressa Pennant, 1777 were used in representation of sessile preys, and the hermit crab Clibanarius erythropus (Latreille, 1818), the toothed top shell Phorcus lineatus (da Costa, 1778) and the rock sea urchin Paracentrotus lividus (Lamarck, 1816) as representatives of vagile prey.…”
Section: Target Species and Sampling Sitesmentioning
confidence: 99%
See 2 more Smart Citations